(untitled) (Jurnal Adabiya, 2025)
This study aims to assess the level of Mendeley literacy among students in the Family Welfare Education Study Program at Syiah Kuala University, focusing on three key aspects: general understanding, theoretical comprehension, and practical application. The research is motivated by an academic policy mandating the use of Mendeley for academic writing, particularly in undergraduate theses. However, the extent of students’ actual understanding of the software remains unclear. A quantitative descriptive approach was employed, with data collected via a Google Form-based test comprising 50 multiple-choice questions developed from comprehension indicators proposed by Sanjaya (2008). The respondents were active students from the 2020–2021 cohorts in two concentrations: Culinary and Fashion. A total of 215 students were initially considered, with the final sample of 68 determined using purposive sampling and calculated using Slovin’s formula. The findings indicate that students’ overall Mendeley literacy falls into the moderate category, with an average score of 69%. The general and practical understanding aspects each scored 70%, while theoretical comprehension was slightly lower at 66%. Students exhibited proficiency in basic functions and practical usage, such as account creation, reference management, and bibliography generation. However, they faced challenges in more advanced theoretical and technical aspects, including metadata understanding, synchronization algorithms, and deduplication features. These results highlight the need for enhanced training, intensive guidance, and accessible self-learning resources to improve students’ information literacy comprehensively. The study recommends collaboration between lecturers, librarians, and program administrators to strengthen students’ skills in effectively utilizing academic reference management tools.